Liver‐related and extrahepatic events in patients with non‐alcoholic fatty liver disease: a retrospective competing risks analysis. Issue 5 (5th January 2022) - Pennisi, Grazia; Enea, Marco; Romero‐Gomez, Manuel; Viganò, Mauro; Bugianesi, Elisabetta; Wong, Vincent W.‐S.; Fracanzani, Anna Ludovica; Sebastiani, Giada; Boursier, Jerome; Berzigotti, Annalisa; Eslam, Mohammed; Ampuero, Javier; et al.
Summary: Background & Aim: Non‐alcoholic fatty liver disease (NAFLD), and especially fibrotic non‐alcoholic steatohepatitis, is associated with high risks of liver‐related events (LRE) and extrahepatic events (EHE). We evaluated the competitive risk occurrence of LRE and EHE in a large cohort of biopsy‐proven NAFLD stratified according to baseline severity of fibrosis. Methods: Two thousand one hundred thirty‐five patients with biopsy‐proven NAFLD were enrolled. Observed cumulative incidence functions (CIFs) were used to evaluate the risk of LRE and EHE; cause‐specific Cox model and predicted CIFs were fitted to identify predictors of LRE and EHE. A replication cohort of NAFLD patients with liver fibrosis severity estimated by liver stiffness measurement by transient elastography was also enrolled. Results: Observed CIFs indicated that the 60‐month probabilities of LRE and EHE were 0.2% and 3% in F0‐F1, 2% and 3.8% in F2 and 9.7% and 6.4% in F3‐F4 patients, respectively. The cause‐specific Cox model indicated that in F0‐F1 and F2 patients, age > 50 years (HR 2.7) was the only predictor of LRE, while age > 50 years (HR 2.96), previous cardiovascular events (CVE, HR 2.07), and previous extra‐hepatic cancer (HR 2.36) were independent risk factors for EHE. In F3‐F4 patients, age > 55 years (HR 1.73), obesity (HR 1.52), PLT < 150 000/mmc (HR 3.66) and log(GGT) (HR 1.77) were associated with LRE, while age > 55 years (HR 1.74) and previous CVE (HR 2.51) were independent predictors of EHE. Predicted CIFs for HE and EHE in F0‐F1, F2 and F3‐F4 patients stratified the risk of events. The results were externally replicated. Conclusion: The likelihood of EHE in NAFLD patients is relevant and increases according to the severity of liver fibrosis, while the risk of LRE is negligible in F0‐F1, low but clinically relevant in F2 and high in F3‐F4 patients. Abstract : Liver‐related events and extrahepatic events by competing risks analyses in 2135 patients with histological diagnosis of NAFLD, and 2790 patients with clinical diagnosis of NAFLD where fibrosis was estimated by liver stiffness by transient elastography.